Surat Paksa dalam Penagihan Pajak Kendaraan Bermotor dan Bea Balik Nama Kendaraan Bermotor Terhadap Peningkatan Pendapatan Daerah Provinsi Maluku - Heillen Martha Yesephine Tita (Perspektif Hukum, 2016)
Regulations on the national taxation have explicitly regulated the obligations that are inherent in the status of ownership of motor vehicles. It means that the obligation to pay taxes is a responsibility the person or entity as the owner of motor vehicles shall carry out based on the provisions of prevailing regulations on the taxation. Therefore, the retard the owner of the motor vehicles undertakes in carrying out the obligations of taxations constitutes a serious problem in Maluku province. In fact, the coercion letter issued by the Genderal Directorate of Taxation as a means to give warning to the owner of motor vehicles who neglect to pay off the tax debts and transfer tax of the motor vehicles does not still function well and still violates the determined procedures that, therefore, contributes to the regional revenue in taxes.